Manajemen Strategi Pemasaran Alumni SMK Wongsorejo Gombong Kabupaten Kebumen - Imam Subarkah; Juriah Juriah; Imam Satibi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2021)
Competition for graduate work placements in DU/DI which is the government's policy on the SMK curriculum is the main factor behind the implementation of the research. This study takes the formulation of the problem on how to plan, implement and evaluate marketing strategy management for the alumni of SMK Wongsorejo Gombong, Kebumen Regency. The implementation of education is approached with descriptive qualitative and phenomenological methods. The implementation of strategic marketing management for the alumni of SMK Wongsorejo Gombong begins with conducting a SWOT analysis which then results in planning, implementing, and evaluating the marketing strategy of the alumni of SMK Wongsorejo Gombong. The implementation of the alumni marketing strategy is carried out through school collaboration in three ways, namely collaboration with DU/DI, collaboration with parents/guardians, and collaboration with the community. A SWOT analysis related to the planning of the school's annual work program, the preparation of a public relations and Hub in work program which is a core part of alumni marketing is an important step for the school. The involvement of DU/DI and the community can increase the absorption of alumni in the world of work.